Banana peel in dyeing of polyamide/elastane blend fabric. (3rd June 2019) - Yıldırım, Leyla; Erdem Ìşmal, Özlenen
Abstract : Purpose: The purpose of this paper is to show the dyeing effect of banana peel on polyamide fabric by using various mordants and to reveal alternatives to metallic mordants. Design/methodology/approach: The simultaneous mordanting method was used in the dyeing process. Findings: From environmental and economical points of view, this paper studies the use of a natural waste product in textile dyeing. Assessment of domestic organic wastes will provide new possibilities for valorization of biomaterials. It is concluded that colorimetric data are affected by the amount of plant used in extraction, amount and type of mordant and pH of dye bath. Tin II chloride ensured the lightest color shades. No alternative mordants could be presented to iron II sulfate and tin II chloride, as they generated completely different color shades. Acids can be an alternative to 0.8 g/L alum mordant. Ammonium sulfate and sodium acetate also generated similar colors to alum. Ammonium sulfate can be substituted for citric acid and alum. Banana peel can be considered as a natural dye source for polyamide elastane blend fabric. Originality/value: Banana peel can be suggested as a natural colorant with good wash fastness for dyeing of polyamide elastane blend fabric.